Quality assistance for MI Muhammadiyah, Salam District towards a great madrasa with dignity - Irham Nugroho; Rani Nur Apriana; Santi Andriani; Ulfa Nur Aeni; Fahmi Muhammad Hafidh; Riza Ahmad Nurrokhman (Universitas Muhammadiyah Magelang, 2022)
This service activity is aimed at improving the quality of MI in order to create a great Madrasa with dignity. This activity uses a participatory rural appraisal (PRA) approach which is carried out in three stages, namely socialization, training, and mentoring. Through training and mentoring, the potential and quality of education personnel has increased. Moreover, the service team is renovating the infrastructure, so that it can support the effort to create a great and dignified madrasa.